Quality of Heterogeneous Mobile Data Services: Capabilities and End-user Achievements - Batkauskas, V.; Kajackas, A. (Elektronika ir Elektrotechnika, 2010)
Then analyzing quality characteristics of different segments of the telecommunication network it was noticed that bandwidth, delay of packets and reliability of the last-mile of the end-users are worse and less stable than in the core network of the system. It means that the bottleneck of QoS of end-users is in the radio access of the last-mile therefore different users receive different QoS. The goal of this paper is to investigate possibilities of end-users to receive service quality, defined by the network operator. It is also important to analyze dependency of the received data throughput of the end-user on the distance to the base station and time in the fixed position. It was proved theoretically and practically that the downlink throughput, achieved by the end-user depends very much on the location of the user in the coverage area and time.